PATERNAL EMOTIONAL SUPPORT, INFANT TEMPERAMENT, AND BREASTFEEDING DURATION AT PUSKESMAS BOGOR TIMUR IN 2026 - Afrina, Rina; Tuti Rusmiati (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2026)
The duration of breastfeeding determines the success of exclusive breastfeeding in mothers after giving birth. Emotional support from fathers and the temperament of babies can be factors that cause the cessation of breastfeeding. This study aims to analyze the relationship between emotional support from fathers and the temperament of babies with the duration of breastfeeding. This is a descriptive observational study with a cross-sectional design. The sampling technique used accidental sampling with a total of 55 mothers in the eight-week postpartum period. This study was conducted during December-January 2026 at the Bogor Timur Community Health Center. The research instruments were the Partner Breastfeeding Influence Scale (PBIS), Infant Characteristic Questionnaire (ICQ), and breastfeeding duration questionnaire. Univariate data analysis used frequency distribution and bivariate analysis used the chi-square test. The results showed that the father's emotional support was in the low category (54.4%), the infant's temperament was easy (50.9%), and the duration of breastfeeding was less than 1 month (54.5%). Paternal emotional support and infant temperament were significantly associated with infant breastfeeding duration (p=0.000 and p=0.001 <0.05). During the breastfeeding period, mothers need paternal emotional support and a more stable infant temperament.